Self-rated health and mental health of lone fathers compared with lone mothers and partnered fathers: a population-based cross-sectional study. Issue 5 (6th December 2016) - Chiu, Maria; Rahman, Farah; Kurdyak, Paul; Cairney, John; Jembere, Nathaniel; Vigod, Simone
Abstract : Background: Lone parenthood is associated with poorer health; however, the vast majority of previous studies have examined lone mothers and only a few have focused on lone fathers. We aimed to examine the self-rated health and mental health status among a large population-based cross-sectional sample of Canadian lone fathers compared with both partnered fathers and lone mothers. Methods: We investigated differences in self-rated health and mental health among 1058 lone fathers compared with 20 692 partnered fathers and 5725 lone mothers using the Ontario component of the Canadian Community Health Survey (2001–2013). Multivariable logistic regression was used to compare the odds of poor/fair self-rated health and mental health between the study groups while adjusting for a comprehensive list of sociodemographic factors, stressors and lifestyle factors. Results: Lone fathers and lone mothers showed similar prevalence of poor/fair self-rated health (11.6% and 12.5%, respectively) and mental health (6.2% and 8.4%, respectively); the odds were similar even after multivariable adjustment. Lone fathers showed higher odds of poor/fair self-rated health (OR 1.53, 95% CI 1.07 to 2.17) and mental health (OR 2.09, 95% CI 1.26 to 3.46) than partnered fathers after adjustment for sociodemographic factors; however, these differences were no longer significant after accounting for stressors, including low income and unemployment. Conclusions: In this large population-based study, lone fathers had worse self-rated health and mental health than partnered fathers and similarly poor self-rated health and mental health as lone mothers. Interventions, supports and social policies designed for single parents should also recognise the needs of lone fathers.